The enigma of the five heavens and early Jewish cosmology1. (June 2019) - Kulik, Alexander
This article proposes an integrative analysis of the ouranology of 3 Baruch . This apocalyptic work, properly read, manifests complex ouranological conceptions well integrated not only into early Jewish literature and Hellenistic thought, but also into later mystical traditions. The unique worldview of the book has heretofore given rise to a complex set of interpretive problems; the detailed comparative approach of the present article not only provides a reasonable solution, but also sheds light on the cosmological conceptions of other early Jewish documents and the traditions lying behind them.